Mononuclear heteroleptic complexes of copper(i) with 5-phenyl-2, 2′-bipyridine and triphenylphosphine: crystal structures, Hirshfeld surface analysis and luminescence properties12. (16th May 2016) - Safin, Damir A.; Vande Velde, Christophe M. L.; Babashkina, Maria G.; Robeyns, Koen; Filinchuk, Yaroslav
Abstract : The complexes [CuL(PPh3 )Hal] (L = 5-phenyl-2, 2′-bipyridine, Hal = Cl −, Br − ) are emissive in the solid state at 298 K, with maxima at 596 and 610 nm, respectively, due to a (M + Hal)LCT excited state. Abstract : The reaction of 5-phenyl-2, 2′-bipyridine (L ) with a mixture of CuCl or CuBr and PPh3 leads to the formation of mononuclear heteroleptic complexes [CuL(PPh3 )Cl] (1 ) and [CuL(PPh3 )Br] (2 ). According to X-ray diffraction, 1 and2 crystallize in the triclinic P 1̄ and orthorhombic Pbca space groups, respectively. The structure of1 contains four independent molecules in the asymmetric unit. Both structures reveal that each tetracoordinated copper(i ) atom is linked to the two nitrogen atoms ofL, one halogen and one PPh3 with the formation of a slightly distorted trigonal pyramidal coordination core. Both structures are additionally stabilized by weak intramolecular π⋯π stacking interactions formed between the terminal pyridine fragments of two ligandsL corresponding to two adjacent molecules. Hirshfeld surface analysis showed that the structures of both complexes are highly dominated by H⋯H and H⋯C contacts and also characterized by H⋯Hal, C⋯C, H⋯N and C⋯N contacts. Both1 and2 were found to be emissive in the solid state at 298 K, with maxima at 596 and 610 nm, respectively, due to a (M + Hal)LCT excited state. The observed blue-shifting of the emission maximum of1 and2 compared to that of the previously reported [CuL(PPh3 )I] can be explained by the replacement of the iodide by a weaker electron-donating bromide and chloride, respectively, lowering the HOMO energy level, less influencing the LUMO energy, and thus resulting in an increase of the HOMO–LUMO energy gap. This explanation is further supported by comparison with the recently reported emission maxima at 630 and 575 nm of the closely related complexes, namely [CuL(PPh3 )I] and [CuL(PPh3 )2 ]BF4, respectively. The emission maxima of1, 2 and [CuL(PPh3 )I] are slightly (12–16 nm) shifted to longer wavelengths when the temperature was lowered to 77 K.